Development of indirect sandwich ELISA for determination of excretory-secretory antigens of Fasciola hepatica - Alzamora-Gonzales, Libertad (2016)
Fasciolosis is a cosmopolitan parasitosis medical-veterinary importance caused by Fasciola hepatica, which affects sheep, goats and cattle; and it affects man accidentally causing an epidemic-endemic infection difficult to diagnose. The aim was to develop an indirect sandwich ELISA with 3 antibodies for detecting excretory-secretory antigens of Fasciola hepatica (ESFh). For the development of indirect sandwich ELISA were used, as capture antibody, mouse polyclonal antibodies anti ESFh and polyclonal antibodies rabbit anti-ESFh as detection antibody, at the concentrations of 10 and 5 µg/mL respectively. The conjugate used was mouse monoclonal anti- total immunoglobulins rabbit linked to peroxidase (1/1000). Were analized 31 sheep fecal samples, and the results were compared with those obtained by direct coproparasitological examination (DC) and counterimmunoelectrophoresis (CIEP). The detection limit obtained for indirect sandwich ELISA was 100 ng/mL. The test had a 100% sensitivity, 96.6% specificity, positive and negative predictive values of 50% and 96.6% respectively, in relation to DC test. Comparing with CIEP the specificity obtained for indirect sandwich ELISA was 93.5% and a negative predictive value of 100%. We concluded that indirect sandwich ELISA designed is able to detect metabolic antigens in ovine feces samples and can be used for Fasciola hepatica diagnosis.